2022
DOI: 10.48550/arxiv.2207.04071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generating cosmological perturbations at Horndeski bounce

Abstract: We construct a concrete model of Horndeski bounce with strong gravity in the past. Within this model we show that the correct spectra of cosmological perturbations may be generated at early contracting epoch, with mild fine-tuning ensuring that the scalar spectral tilt n S and tensor-to-scalar ratio r are consistent with observations. The smallness of r is governed by the smallness of the scalar sound speed. Arbitrarily small values of r are forbidden in our setup because of the strong coupling in the past. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…To clarify this point, let us follow refs. [86][87][88][89][90][91][92]. In terms of the canonically normalized tensor fluctuation v ij = aM p h ij /2 denoted by v below, one obtains…”
Section: Dynamical Couplingmentioning
confidence: 99%
“…To clarify this point, let us follow refs. [86][87][88][89][90][91][92]. In terms of the canonically normalized tensor fluctuation v ij = aM p h ij /2 denoted by v below, one obtains…”
Section: Dynamical Couplingmentioning
confidence: 99%
“…The obtained models are stable, and the perturbations above the background in them are not superluminal. In their new paper [3], Yu A Ageeva, P K Petrov, and V A Rubakov have substantially developed and justified this class of models. They show that cosmological primordial perturbations can be generated in them with a spectrum which is necessary for galaxy formation and is observed in relic radiation perturbations.…”
mentioning
confidence: 99%
“…They show that cosmological primordial perturbations can be generated in them with a spectrum which is necessary for galaxy formation and is observed in relic radiation perturbations. It is interesting that perturbations in model [3] are generated at the stage of previous compression before the contemporary expansion. Thus, it was shown that the Universe may have evolved in nontrivial ways, and, being consistent with the observational data, the new wide class of cosmological models is admissible.…”
mentioning
confidence: 99%